2023
DOI: 10.7759/cureus.33286
|View full text |Cite
|
Sign up to set email alerts
|

Platelet, Mean Platelet Volume and Platelet Distribution Width Levels Might Be a Promising Marker for the Prediction of Disease Severity, Mucosal Healing and Steroid Dependence in Patients With Ulcerative Colitis

Abstract: Background/aims: In this study, we aimed to determine the value of mean platelet (PLT) volume (MPV), PLT and PLT distribution width (PDW) levels as a marker in the prediction of mucosal healing (MH), steroid resistance (SR) and steroid dependence (SD) in newly diagnosed moderate and severely active patients with ulcerative colitis (UC), who did not receive medical treatment before. Patients/methods: Two hundred forty-nine patients with severely or moderately active UC and 50 healthy subjects were en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
(47 reference statements)
1
1
0
Order By: Relevance
“…In 2023, Gerçeker et al demonstrated that PLT and PDW values are important biomarkers for determining mucosal healing, steroid resistance, and dependence in patients newly diagnosed with moderate-to-severe UC. In addition, the same study reported that PDW values were positively correlated with mucosal healing [65]. The results of this study are consistent with those of the existing literature on the indicators of active disease.…”
Section: Discussionsupporting
confidence: 92%
“…In 2023, Gerçeker et al demonstrated that PLT and PDW values are important biomarkers for determining mucosal healing, steroid resistance, and dependence in patients newly diagnosed with moderate-to-severe UC. In addition, the same study reported that PDW values were positively correlated with mucosal healing [65]. The results of this study are consistent with those of the existing literature on the indicators of active disease.…”
Section: Discussionsupporting
confidence: 92%
“…Studies conducted in patients with ulcerative colitis, appendicitis, and newborns with acute respiratory disorders have revealed a relationship between MPV and the severity of the clinical condition. However, there is no conclusion as to whether the variability in the indicator is only a useful additional diagnostic marker or just one of the parameters affected by the developing inflammatory state [ 44 , 45 , 46 , 47 ]. It is worth emphasizing that a higher MPV is associated with greater platelet activity [ 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%